Aplikasi Mobile Android E-Learning dan Kuesioner pada SMK Muhammadiyah 7 Jakarta - Kusmanto, Tria Hadi (Program Studi Teknik Informatika Universitas Pamulang, 2021)
SMK Muhammadiyah 7 Jakarta already has many learning systems that are applied in learning activities. The use of ICT in learning activities such as the use of internet networks, projector devices, local computers and networks. Basically, this system is sufficient to assist the teaching and learning process and in conducting school research (questionnaire). Teaching and learning is a process of relations between teachers and students. The questionnaire is a data collection technique by giving written and unwritten questions to get answers from respondents. However, these activities have not been realized in their development, such as using an Android-based learning system and questionnaire. In accordance with this explanation, an application is needed to assist the teaching and learning process and school research (questionnaire). This research was conducted to realize the development of an android-based system.